Propuesta de diseño conceptual de un equipo de aire acondicionado para el proyecto de la empresa Aconaire S.A.S. de acondicionamiento de quirófanos (2018)
The present project was developed in order to offer an alternative design of an air conditioning equipment adjusted to the characteristics established by the clinic of the worker and Aconaire SAS, in order to ensure conditioning and air quality in the operating rooms of the clinic The development of the eight chapters was made in order to achieve compliance with the objectives proposed for this degree work, providing an alternative design of the air conditioning equipment applicable to the worker's clinic, it should be mentioned that its implementation will depend on of the criterion of Aconaire SAS It should be borne in mind that chapter three corresponds to the development of the first objective, chapter four responds to the second objective, chapter five covers the third objective and finally chapter six argues the fulfillment of the fourth specific objective.